Professional Development of Teacher Trainers: The Role of Teaching Skills and Knowledge - Su, Hang; Wang, Jialin (Frontiers in Psychology, 2022)
Since the 1990s, the essential function of teacher trainers in academic courses has gradually attained more attention from scholars. Also, the teacher trainers’ professional development has acquired worldwide attraction following the concept that teacher trainers are deeply liable for educator education quality. The present mini-review of literature indicates that while teacher trainers have several complicated functions, they obtain the least preparation or opportunities for professional development to perform such functions. Consequently, they require getting the related knowledge and skills after accepting the role of teacher trainers. Besides numerous aspects affecting teacher trainers’ professional development, teaching skills and knowledge have important functions that are at the center of attention in this mini-review of literature. In brief, several implications are presented for the instructional addressees.